2021
DOI: 10.3389/fpsyg.2021.691183
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Experience and Construction of Personalized Smart Tourism Program Under Tourist Psychology

Abstract: The present work aims to boost tourism development in China, grasp the psychology of tourists at any time, and provide personalized tourist services. The research object is the tourism industry in Macau. In particular, tourists' experiences are comprehensively analyzed in terms of dining, living, traveling, sightseeing, shopping, and entertaining as per their psychological changes using approaches including big data analysis, literature analysis, and field investigation. In this case, a model of tourism experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…is analytical approach can prioritize problems and distinguish strategic objective obstacles from tactical problems. It can also list these research objects, arrange them in the form of a matrix, and use the thinking of systematic analysis to match various factors to each other for analysis, draw a series of corresponding conclusions with specific decision making, which is conducive to leaders and managers to make more correct decisions and planning [29][30][31][32].…”
Section: Swot Analytical Methodmentioning
confidence: 99%
“…is analytical approach can prioritize problems and distinguish strategic objective obstacles from tactical problems. It can also list these research objects, arrange them in the form of a matrix, and use the thinking of systematic analysis to match various factors to each other for analysis, draw a series of corresponding conclusions with specific decision making, which is conducive to leaders and managers to make more correct decisions and planning [29][30][31][32].…”
Section: Swot Analytical Methodmentioning
confidence: 99%
“…Finally, a computer-readable model is designed and constructed, which can accurately express users' interest preferences and effectively obtain the changes of their interests. In all kinds of personalized recommendation service platforms, only by establishing an accurate user interest model can we carry out the next project matching, intelligent push and other related work 10 . The process of interest modeling is shown in Figure 1.…”
Section: The Basic Theory Of Tourism Service Recommendation 21 Person...mentioning
confidence: 99%
“… Mihalič (2000) reported that tourist destinations, tourist routes, and the tourism industry are the main factors to use when measuring tourism competitiveness. Scholars have found that the main influencing factors of tourism competitiveness are human resources, talent competition, image marketing, and knowledge-based management ( Wei, 2000 ; Nie, 2006 ; Zhang et al, 2011 ; Cvelbar et al, 2016 ; Yang et al, 2020 ; Lan et al, 2021 ). In addition, tourists’ perceptions and the level of scientific and technological development of tourist destinations have a significant impact on the competitiveness of urban tourism destinations.…”
Section: Literature Reviewmentioning
confidence: 99%